School - Based Conflict (Case Study at a State Junior High School in Sigi District) - Sudin Sudin; Muhammad Nur Ali; Ilyas Lampe (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research aims to describe conflict cases that occurred in SMP Negeri in Sigi District; Analyzing the role of the Sigi District Education and Culture Service Government in resolving conflict cases at State Junior High Schools in Sigi Regency; Analyzing school policies in resolving conflict cases at State Junior High Schools in Sigi District. To answer the questions in the research, a case study approach was carried out, a qualitative approach and this type of research was descriptive.. The data analysis technique used an interactive approach from Miles and Huberman which consists of data collection, data reduction, data presentation, data verification, and drawing conclusions. The research showed three results. First, the case of conflict in the State Junior High School in Sigi District occurred interpersonally, namely the conflict between students and students triggered by playful behavior; teachers and students are triggered by violations of school rules; teacher and teacher triggered mutual belittlement and selfishness; principals with teachers because teachers teach not optimally; and teachers with parents of students triggered by parental defense. Second, the role of the government related to conflict resolution and resolution in public junior high schools in Sigi District acts as a mediator in overcoming conflicts that cannot be handled at school. Third, school policies in dealing with and resolving conflicts in schools are carried out in a conventional way, namely conflict resolution is carried out with the same method before, namely, giving advice, dialogue with related parties, giving sanctions, suspensions, returning students to their parents, art approaches, transfers, delaying the payment of certification and the issuance of a statement (agreement), finally formed the concept of implementing policy spiraling in schools.